Identification of Four Novel COL4A5 Variants and Detection of Splicing Abnormalities in Three Chinese X-Linked Alport Syndrome Families - Wang, Sai; Shao, Yingfei; Wang, Yixiu; Lu, Jingru; Shao, Leping (Frontiers in genetics, 2022)
Chronic renal disease associated with X-linked Alport syndrome (XLAS) is relatively rare. However, due to the lack of specificity in the pathologic and clinical manifestations of the disease, it is easy to be misdiagnosed. In this study, we included three Chinese families with XLAS and used targeted NGS to find gene variants. In family X1, the 36-year-old male proband had hematuria, massive proteinuria, sensorineural deafness and ESRD at 33. In silico prediction showed the novel c.1424-4C > G variant reduced the score of the normal 3’ splice site from 0.47 to 0.00 (according to BDGP). Transcriptional analysis from his peripheral blood cells indicated that it caused the insertion of an amino acid [p.(Lys474_Gly475insVal)]. In family X2, the proband was a 32-year-old male, who had hematuria, proteinuria, hypertension, hearing loss and progressed into ESRD at 30 years. He carried a novel missense variant c.2777G > T p.(Gly926Val). In family X3, the proband, a 16-year-old male, had hematuria, massive proteinuria, sensorineural deafness and ESRD; the results of renal pathological findings were consistent with AS. He carried a novel variant c.4529-2A > T, so did his mother with ESRD and probable XLAS. Bioinformatic analysis with BDGP showed that it abolished the acceptor site from 0.83 to 0.00. RT-PCR analysis from his kidney tissue indicated that it caused exon 50 skipping and exon 50 skipping along with inserting a cryptic exon derived from intron 49 p.[Gly1510Aspfs*11, Gly1510Alafs*35]. Another novel missense variant c.1552G > A p.(Gly518Arg) was identified in his mother and his aunt. No skewed X-chromosome inactivation was involved in these two female patients. In conclusion, four novel variants in COL4A5 were identified and transcriptional analysis is essential to investigate the pathogenicity of intronic variants. Thus we found a rare event in a female patient with XLAS caused by two COL4A5 variants in trans .